Association of anti‐cyclic citrullinated peptide antibodies and rheumatoid factor isotypes with HLA‐DRB1 shared epitope alleles in Egyptian rheumatoid arthritis patients. (13th March 2020) - Raslan, Hala M.; Attia, Hanaa R.; Hamed Ibrahim, Mona; Mahmoud Hassan, Eman; Salama, Iman I.; Ismail, Sherif; Abdelmotaleb, Eman; El Menyawi, Manal M.; Amr, Khalda S.
Abstract: Introduction: The most common genetic risk factor for rheumatoid arthritis (RA) is human leucocyte antigen DRB1 (HLA‐DRB1) shared epitope (SE). Aim: To investigate the relationship between anti‐cyclic citrullinated peptide (anti‐CCP), rheumatoid factor (RF), immunoglobulin (Ig)G, IgM and IgA and HLA‐DRB1 SE among Egyptian patients with RA. Methods: Serum levels of anti‐CCP antibodies and RFIgG, RFIgM, RFIgA were assayed using enzyme‐linked immunosorbent assay for 157 Egyptian RA patients and 150 healthy controls attending the outpatient clinics of National Research Center and Kasr El Aini Hospital. HLA‐DRB1 genotyping was performed by the DynalAllSetTM polymerase chain reaction (PCR) single specific primer low‐resolution typing kits. Amplified PCR product was checked using 3% agarose gel. Results: HLA‐DRB1‐SE was found among 129 (82.2%) RA patients and 67 (44.7%) controls (odds ratio [OR] 5.7, CI 3.4‐9.6, P  < .0001). The risk of RA development was higher with the presence of SE two alleles (OR 11.6, P  < .0001), while the OR for 1 copy SE allele was 4.4 ( P  < .0001). HLA‐DRB1‐ SE was significantly associated with positive as well as negative anti‐CCP and RF isotypes. The stronger association was with anti‐CCP positivity with OR 11 (5.1‐23.6), P  < .0001. Furthermore, the risk of development of positive anti‐CCP and RF isotypes was higher with the presence of 2 copies of SE alleles than with 1 copy. Conclusion: The prevalence of HLA‐DRB1‐SE is high in Egyptian RA patients. The role of SE in RA patients is most probably related to the development of anti‐CCP positive RA rather than the development of anti‐CCP positivity.